Perceptions of students about drug consumption and risk factors at a public shcool in Brasilia, Brazil - Lima, Maria da Glória; Paz, Ana América Magalhães; Gussi, Maria Aparecida; Dias, Raquel da Cruz (Tempus – Actas de Saúde Coletiva, 2011)
The purpose of this research was to develop an interdisciplinary educational activity in a school setting, based on the concept of health promotion, by providing spaces for reflection, verbalization and information about the issue of drugs and its associated factors. Data was collected at a primary education public school of the Federal District Federal from 52 sixth graders aged 11 to 13, through freeexpression workshops in which the students openly discussed the theme in groups as well as provided a record of drawings, poetry, essays. The results were analyzed through content analysis and theme categorization. The results showed that adolescents have some knowledge about risk factors of drug use for its users and for the social environment. However, their narratives reveal that they are vulnerable to risk factors through early exposure to drugs, behavior and communication patterns within their families and possible influence of peers groups who don´t always act as a shielding system. It is evident the need for school to involve families and other resources in society into forming a protective network for adolescents to deal with their vulnerability and minimize the drug damage. Information, youth leadership, healthy habits, the strengthening of health promotion and prevention models in the scope of the surroundings, as well as dialogue between school and family must become priorities so that the relation subject drugconsumption can be faced, in a concrete and positive manner, in the education of young people and organization of society.